AQUATIC INSECT LARVAE AS AN INDICATOR OF ECOLOGICAL INTEGRITY OF PANASEN UPSTREAM, TONDANO WATERSHED, NORTH SULAWESI - Ireana Yusra, Abdul Fatah; Fathurrahman, Lananan (2018)
The upstream ecological integrity facing anthropogenic pressures has been assessed linked to the community of aquatic insect larvae inhabiting. This paper evaluate the ecological integrity of the Panasen Stream by determining the distribution and environmental parameters affecting the community of aquatic insect’s larvae in the Tondano Watershed. Physical and chemical parameters such as temperature, velocity, pH, Dissolved Oxygen, Conductivity, Turbidity, Hardness, Total Suspended Solids, Ammonia and Total Phosphate Water were collected. PCA analysis showed that current velocity, depth and width of the stream greatly affected the distribution and abundance of aquatic insect larvae, precipitation and substrate. Land use and active volcanic results in unsustainable anthropogenic activities have contributed to lowering the water quality, low species richness and weak ecological integrity of the Panasen Stream